Strengthening a Model of Community Food Security in Central Java During the Pandemic - Subowo, Ari; Yuniningsih, Tri; Herawati, Augustina Rina (KnE Social Sciences, 2022)
Achieving food and nutrition security for all people remains one of the defining challenges for humanity in the 21st century. The crisis related to strengthening food security during the Covid-19 pandemic has become a global concern. The World Food Program states that despite developments in agricultural technology, micronutrient deficiencies and stunting remain problems. The purpose of this study was to determine the pattern of food and non-food consumption of the community in Temanggung Regency, as well as the efforts in dealing with community food security. A qualitative approach was used in analyzing a model to formulate policies for strengthening community food security during the COVID-19 pandemic. The results showed that the Temanggung Regency Government has designed an intervention by preparing a strategic plan and implementing a cross-sectoral approach. The policy programs and activities relate to food safety, quality of food intake and nutrition. However, according to the results, promoting food security in villages does not guarantee a decrease in malnutrition, and in some villages such as Kalimangis, the health status of children has actually deteriorated. The relationship between food security and family nutritional conditions is not linear due to factors related to environmental health, cleanliness and healthy lifestyle behaviors. Therefore, interventions in the field of food security have to be followed by interventions related to personal health status and environmental conditions. Keywords: food security, program intervention model, environmental health